2019
DOI: 10.33701/ijok.v3i2.591
|View full text |Cite
|
Sign up to set email alerts
|

Bureaucratic Reform and The Challange of Good Governance Implementation in Indonesia

Abstract: Bureaucratic reformation is the fundamental structuring efforts are expected to havean impact on changing systems and structures. The system deals with the relationshipbetween the unsure or the element that influence each other and are associated to makea form totally. The change in one element can influence the other elements in the system.The structure relates with the order of who arrayed a regular basis and systematically.Structure changes is also included with the mechanism and procedure, human resources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
11
1
2
Order By: Relevance
“…Next, hypothesis test was conducted on hypothesis 2, and the result indicated that BR has a positive but not significant effect on GFP, with p-value of >0.1 and path coefficient value of 0.124, which signifies that those results are rejecting hypothesis 2. These results are not consistent with previous findings, which said that BR can improve GFP (Labolo & Indrayani, 2017;Gaus et al, 2016). However, those results are supporting Ria et al (2016) who discovered that BR does not have effect on financial performance but does greatly affect public service and people welfare.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…Next, hypothesis test was conducted on hypothesis 2, and the result indicated that BR has a positive but not significant effect on GFP, with p-value of >0.1 and path coefficient value of 0.124, which signifies that those results are rejecting hypothesis 2. These results are not consistent with previous findings, which said that BR can improve GFP (Labolo & Indrayani, 2017;Gaus et al, 2016). However, those results are supporting Ria et al (2016) who discovered that BR does not have effect on financial performance but does greatly affect public service and people welfare.…”
Section: Resultscontrasting
confidence: 88%
“…Indeed, BR is designed to create a transparent and accountable bureaucracy in serving public interest (Kasim, 2013). Moreover, Hajar (2015) declared that BR allows the government to build capacity to enhance public service scope, to establish bureaucracy that is professional, clean, accountable, neutral and effective, which can serve public interest, and also to create democratic governance management to achieve better GFP (Labolo & Indrayani, 2017;Gaus et al, 2016). In regard of all the findings above, it can be said that BR has a positive effect on GFP.…”
Section: The Effect Of Br On Gfpmentioning
confidence: 99%
“…Pelayanan publik yang berkualitas dapat diwujudkan melalui perilaku-perilaku positif yang ditampilkan oleh segenap jajaran petugas dan pimpinan di unit terdepan pemerintahan. Artikel ini merujuk pada konsep Good Corporate Governance (Rusydi, Palutturi, Noor, & Pasinringi, 2020) di sektor swasta atau Good Governance di sektor publik (Labolo & Indrayani, 2017). Dalam konsep tersebut dijelaskan bahwa untuk menjalankan praktek pengelolaan aktivitas dan sumber daya yang dimiliki oleh organisai, para pelaksana (mulai dari pimpinan tertinggi sampai dengan pelaksana lapangan terendah) haruslah menjalankan kegiatan tata kelola berbasis dengan perilaku T-A-R-I-F, yaitu: (1) Transparencesetiap kegiatan yang dijalankan dapat ditelusuri dengan mudah diakses oleh publik, (2) Accountablekegiatan-kegiatan yang telah dilalkukan dapat diidentifikasi siapa penangggung jawabnya, (3) Responsiblepetugas bersedia melakukan Tindakan tanggung jawab bila dikemudian hari muncul dampak negatif dari pelaksanaaan tuagas, (5) Integritypetugas menjalankan nilai-nilai kejujuran dan menghindarkan diri dari perbuatan mengambil keuntungan pribadi atas tugas dan wewenang yang dimiliki, dan (5) Fairnessberperilaku adil lebih mengutamakan kepentingna masyarakat daripada diri sendiri dan golongan tertentu Bila mengacu pada pendekatan organizational behavior (Scandura, 2017) dan positive reinforcement theory (Skinner, 2014), perilaku dipengaruhi oleh antesenden dan konsekuensi.…”
Section: T-a-r-i-f Behavior Sebagai Praktek Good Governanceunclassified
“…Bureaucratic reform is carried out in the context of realizing good governance, where bureaucratic reform is a strategic step to build a state civil apparatus so that it is more qualified in carrying out general duties of government, as an organizer of public services with the aim of meeting community needs in the form of goods or services in accordance with standards and the rules that have been set (Cope, 1997;Labolo & Indrayani, 2017). The Indonesian bureaucracy has always been a public opinion that never gets boring, this is because until now the bureaucracy in Indonesia is still problematic and far from what was expected (Wihantoro et al, 2015;Iqbal, 2020).…”
Section: Inroductionmentioning
confidence: 99%